FRAUD AND WHISTLEBLOWING IN THE MANAGEMENT OF STUDENT FUNDS - Aprina Nugrahesthy Sulistya Hapsari; Edi Supriyono (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
The aim of this study was to find out whether there is the potential for fraud and whistleblowing in the management of student funds as a way to detect fraud in universities. The type of research used in this study was descriptive qualitative research. Data collection was done through interviews, observation, and documentation. This study was conducted at one of universities located in Central Java by describing several variables including fraud, whistleblowing and management of student funds.. The data was analyzed using fraud triangle framework and the fraud scheme based on the ACFE classification. The results of this study show that in the management of student funds there was the potential for fraud, such as misuse of financial statements and corruption. There was indication of fraud, but it did not happen. Potential for whistleblowing was not found because they assume that if fraud occurs it is better to discuss it in a family manner and will not report it.